Polarographic Determination of Stability Constant Values of In(III) Complexes with Amino Acids by DeFord and Hume’s and Mihailov’s Methods - SINGH, JYOTI; GUPTA, O.D. (Asian Journal of Chemistry, 2010)
The reduction of In(III) with amino acids (serine, leucine, isoleueine) has been investigated electrochemically in aqueous medium and the stability constants of complexes formed by In(III) with these amino acids have been evaluated. The complexes of metal with amino acids ratio as 1:1, 1:2, 1:3 have been reported. The values of stability constants of complexes of In(III) with serine are log b1 = 7.0988, log b2 = 7.3086, log b3 = 7.3108 and complexes of In(III) leucine have log b1 = 5.1363, log b2 = 6.4771, log b3 = 7.3247 and complexes of In(III) with isoleucine have log b1 = 4.3222, log b2 =4.4051, log b3 = 4.5051 at 308 K which have been calculated by DeFord and Hume's method. The mathematical Mihailov's method was also used.